Clinical significance of evaluating endoscopic response to neoadjuvant chemotherapy in esophageal squamous cell carcinoma. Issue 1 (17th July 2019) - Nagai, Yohei; Yoshida, Naoya; Baba, Yoshifumi; Harada, Kazuto; Imai, Katsunori; Iwatsuki, Masaaki; Karashima, Ryuichi; Koga, Yuki; Nomoto, Daichi; Okadome, Kazuo; Ishimoto, Takatsugu; Imamura, Yu; et al.
Abstract : Background and Aim: Clinical significance of endoscopic response (ER) after neoadjuvant chemotherapy (NAC) for esophageal cancer has not been fully understood. Thus, the present study aimed to investigate the association between ER to NAC and its clinicopathological outcomes in patients with esophageal squamous cell carcinoma (ESCC). Methods: In total, 141 patients who underwent NAC and subsequent esophagectomy for ESCC were included. ER to NAC was retrospectively evaluated based on macroscopic findings of the primary tumor, which was classified into three categories: endoscopic no response (eNR), endoscopic partial response (ePR), and endoscopic good response (eGR). An endoscopic responder was defined as patients with eGR/ePR. Results: Approximately 89.4% of patients had cStage II–III disease, and 7.1% had pathological complete response. Upon ER evaluation, eNR, ePR, and eGR were observed in 46 (32.6%), 54 (38.3%), and 41 (29.1%) patients, respectively. Pathological responders significantly increased as the ER grade became better. Among preoperative clinical factors, only ER significantly correlated with pathological response in univariate and multivariate analysis. Endoscopic responders showed a significantly better prognosis than did eNR patients ( P  <   0.001), although the overall survival (OS) of the patients with eGR and ePR was equivalent. Endoscopic responder, ypT, ypN, and pathological responder were significant predictors of OS in the univariate analysis, and endoscopic responder, ypN, and pathological responder were independent predictors in the multivariate analysis. Conclusion: This study suggests that ER can be a simple and important tool to predict the pathological response and survival of patients who undergo NAC for ESCC.